Assessing carbon dynamics of irrigated and rainfed potato (Solanum tuberosum L.) cropping systems in the Andean hillside landscape - Martinez Maldonado, Fabio Ernesto (2023)
Because potatoes have low agricultural emissions and a lower average global warming potential, global potato agriculture is viewed as part of a climate-smart agricultural future. However, the contribution of potatoes to mitigation by CO2 sequestration remains little studied. “Andean” potato is cultivated in both industrial irrigated fields and rainfed systems, as a result, productivity and carbon sink capability could be quite different. Currently, there is a lack of crop- atmosphere carbon exchange studies to know the sink or source activity of potatoes under those water regimes. On this account, this research aimed to investigate carbon fluxes dynamics of irrigated and rainfed potato (Solanum tuberosum L.) cropping systems in the Andean hillside landscape. Specifically, an Eddy covariance tower was used to study the response of net ecosystem exchange (NEE), gross primary production (GPP), and ecosystem respiration (Reco) to water availability on potato agroecosystems. Due to water and carbon fluxes are tightly coupled systems, the influence of water availability on NEE was explored by studying water and carbon fluxes interactions. Furthermore, owing to GPP is the main driver of land carbon sequestration, an up-scaling proposal based on photosynthetic light-response curves is proposed for estimating GPP as an alternative when EC measurements are not available. The rainfed potato crop was a CO2 source (positive NEE) mainly due to low growth, biomass development, high water-carbon decoupling, and lower assimilation capacity. The irrigated potato crop sites were a CO2 sink (had the most negative NEE ) and had large magnitudes of GPP during the crop growth, indicating that irrigation is an important mitigation practice. Multilayer models correctly reproduced the behavior of potato GPP when compared to EC measurements, indicating that Upscaling is a reliable alternative.